2022
DOI: 10.3390/antiox11061048
|View full text |Cite
|
Sign up to set email alerts
|

Value-Added Crackers Enriched with Red Onion Skin Anthocyanins Entrapped in Different Combinations of Wall Materials

Abstract: The objective of this study was to encapsulate anthocyanins from red onion skins into different biopolymeric matrices as a way to develop powders with multifunctional activities. Two different variants of powders were obtained using a combination of gelation and freeze-drying techniques and characterized by encapsulation efficiency, antioxidant activity, phytochemical content, and color. Stability during storage and the bioavailability of anthocyanins in the in vitro simulated digestion were also examined. Pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In addition, the water-holding properties of the structure and porosity of the powder particles during drying can be the other considerations for the moisture contents of the powder. Stoica et al (2022) [ 8 ] observed a similar behavior, studying the freeze-drying of red onion skin with different combinations of wall materials.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, the water-holding properties of the structure and porosity of the powder particles during drying can be the other considerations for the moisture contents of the powder. Stoica et al (2022) [ 8 ] observed a similar behavior, studying the freeze-drying of red onion skin with different combinations of wall materials.…”
Section: Resultsmentioning
confidence: 74%
“…Proteins are efficient carriers for biochemicals due to their low cost, biodegradability, and functionalities that allow them to form films, gels, emulsifiers, and hold onto water [ 8 ]. Whey protein (WP) has high nutritional qualities (e.g., great protein content with abundant essential amino acids) and excellent bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The accepted variations of crackers were evaluated for nutrients like energy, carbohydrate, protein, fat, zinc, iron, calcium, phosphorus and non-nutrients like fibre as per the standard procedures [17] .…”
Section: Nutritionalevaluation Of the Accepted Variation Of Crackersmentioning
confidence: 99%
“…A way to reduce the glycemic index in bakery products would be the partial substitution of wheat flour with flours, rich in indigestible carbohydrates. Literature search showed that the blends of acha and pigeon pea [15] , corn silk [16] , red onion skin [17] , pea peel [18] , defatted coconut flour [19] , jelly fish [20] , Hibiscus sabdariffa calyxes' residue [21] , pumpkin seed flour [22] , etc. had been used as prospective ingredients to formulate value added crackers.In this regard, watermelon rind, as a source of fibre and nutraceuticals, is used in this study as a means to reduce the rate of absorption of glucose from crackers.…”
mentioning
confidence: 99%
“…Currently, saffron (E164), beta-carotene (natural and synthetic), lycopene, tomato extract or concentrate (160) and turmeric or turmeric oleoresin (E100) are the colorants from natural sources accepted by the FDA and EFSA [124].…”
Section: Source Of Natural Yellow-orange Colorants As a Potential Rep...mentioning
confidence: 99%